Anidulafungin Usage Profile and its Economic Impact: A Practical Assessment - Brazeiro Brum, Bruna; Comparsi Wagner, Sandrine; Schirmer, Helena; Pacheco Crestani , Riciéli (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2026)
Introduction: Candidemia is a systemic fungal infection associated with healthcare, related to high mortality rates, prolonged hospitalization, and increased healthcare system costs. Therapeutic recommendations include initiating treatment with echinocandins, performing blood cultures, and, for azole-susceptible isolates such as Candida albicans, therapy with fluconazole. Strategies involving antifungal deescalation are important for therapeutic optimization, aiming to reduce fungal resistance, promote patient safety, and apply the concept of pharmacoeconomics within health care institutions. Objective: To characterize the profile of anidulafungin use in Intensive Care Units (ICUs) and to estimate the resource savings generated by its deescalation. Methods: Descriptive retrospective study including adult patients admitted to ICUs, from the Brazilian Unified Health System (SUS), who received anidulafungin prescriptions. Results: A total of 106 patients were analyzed, of whom only 21 (20.4%) had mycological diagnosis, with Candida albicans being the most frequent isolate (47.6%). De-escalation was performed in 6 patients (28.6%), resulting in savings of R$12,378.29. It is estimated that this amount could have increased by R$5,412.84 if de-escalation had been applied in all cases with indication. Conclusions: The de-escalation strategy demonstrated potential to optimize therapy based on mycological diagnosis, reduce institutional costs, and contribute to the rational use of antifungals, avoiding unnecessary exposure to broad-spectrum agents.